STATUS AND SANCTITY OF MYTH - SEVERAL PERSPECTIVES (Annual of the Faculty of Philosophy in Skopje, 2014)
Myths are tales about the Beginning of the world, the cosmogony, the activities of the divine pre-creatures and/or of the sacred ancestors. For the believer; for the religious man who believes in myths, they are true, sacred tales. They are not only real, but also superior to the usual, quotidian, profane reality, because they refer to the Beginning, a condition ontologically and axiologically superior to it. The paper gives a brief outline of the status and the function of myths in the world of the primordial believer, through myths ’powers to reactualise the initial sacredness of the world in a religious context, thereby guaranteeing the safety and ensuring the identity of the believers in the archaic communities. A short sketch of the theoretical interest in myth is offered, from a meta-level and through several perspectives, noting also a few stances in the ritualistic line, according to which rituals precede myths. Attention is paid to the sacredness of myths in several authors who treat myths as superior, paradigmatic and performative tales.
Keywords: MYTH; SACRED; BELIEVER; RITUAL; REACTUALISATION